Pemberdayaan Kelompok Wanita Tani dalam Produksi Mi Mocaf sebagai Produk Unggulan Berbasis Komunitas - yulianti, Amalia; Maulana, Rifky; Nurqaidah, Siti; Talitha, Zada Agna (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Community empowerment through agricultural product processing plays a crucial role in enhancing local economic independence and creating sustainable added value. Sriwedari Village in Lampung Province has abundant cassava-based agricultural potential, yet its added value remains low due to limited community knowledge and skills in agricultural product processing. The Student Organization Capacity Strengthening Program from the Sumatera Institute of Technology was implemented to empower the Women Farmer Group in Sriwedari Village through the development of a superior product in the form of Mocaf-based noodles branded as Cassami. The program aims to improve community economic independence and strengthen the village identity through a sustainable empowerment movement. The methods applied include participatory training and mentoring, covering Occupational Health and Safety training, packaging development, Mocaf and Cassami noodle production, digital marketing strategies, and legality management, including Business Identification Number, Home Industry Food Permit, and halal certification. Evaluation was conducted through observation, interviews, and group performance assessments based on indicators of skills, productivity, and business sustainability. The results showed an increase in production skills, managerial abilities, as well as product quality and competitiveness. Moreover, the Women Farmer Group became capable of independently producing Cassami noodles and expanding online marketing networks. This activity successfully strengthened the synergy between higher education institutions, the community, and the village government in promoting local economic empowerment. Overall, the program contributed to improving community welfare and positioning Sriwedari Village as an innovative center for high-quality Mocaf noodle production.